Validating the Parkinson's disease caregiver burden questionnaire (PDCB) in German caregivers of advanced Parkinson's disease patients. (25th March 2019) - Klietz, M.; Rippena, L.; Lange, F.; Tulke, A.; Paracka, L.; Dressler, D.; Wegner, F.
ABSTRACT: Background: Advanced Parkinson's disease (PD) may place a high burden on patients and their caregivers. Understanding the determinants of caregiver burden is of critical importance. This understanding requires the availability of adequate assessment tools. Recently, the Parkinson's disease caregiver burden questionnaire (PDCB) has been developed as a PD-specific measure of caregiver burden. However, the PDCB has only been evaluated in a sample of Australian caregivers of patients at a less advanced stage of the disease. Objective: We tested whether a German translation of the PDCB qualifies as an adequate measure of caregiver burden in a German sample of caregivers of advanced patients with PD. Methods: We collected PDCB data from 65 caregivers of advanced patients with PD. Reliability of the scale was assessed and compared against the original version. To validate the German version of the PDCB, we examined the correlations with the caregiver burden inventory (CBI), the short form 36 health survey (SF-36), the Parkinson's disease quality of life questionnaire 39 (PDQ-39), disease duration, and the amount of caregiving time. Results: The total PDCB score proved to be reliable and to be significantly related to CBI and SF-36 scores. PDCB scores also increased with increasing amounts of caregiving time. Conclusions: The German version of the PDCB appears to be an adequate measure of caregiver burden in caregivers of advanced PD patients.